Nâng cao chất lượng quản lý và khai thác nguồn tài liệu số nội sinh tại Thư viện Trường Đại học Sư phạm- Đại học Thái Nguyên - Vương, Hồng Hải (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article presents the concept, nature and meaning of institutional digital resources; Analyze the current situation of the management and exploitation of endogenous digital resources and propose some solutions to improve the quality of management and exploitation of institutional digital resources at the Library of the University of Education - Thai Nguyen University.